Long-Term Outcomes of Hypertrophic Cardiomyopathy Diagnosed During Childhood: Results From a National Population-Based Study. Issue 1 (3rd July 2018) - Alexander, Peta M.A.; Nugent, Alan W.; Daubeney, Piers E.F.; Lee, Katherine J.; Sleeper, Lynn A.; Schuster, Tibor; Turner, Christian; Davis, Andrew M.; Semsarian, Chris; Colan, Steven D.; Robertson, Terry; Ramsay, James; et al.
Abstract : Background: Late survival and symptomatic status of children with hypertrophic cardiomyopathy have not been well defined. We examined long-term outcomes for pediatric hypertrophic cardiomyopathy. Methods: The National Australian Childhood Cardiomyopathy Study is a longitudinal population-based cohort study of children (0–10 years of age) diagnosed with cardiomyopathy between 1987 and 1996. The primary study end point was time to death or cardiac transplantation. Results: There were 80 patients with hypertrophic cardiomyopathy, with a median age at diagnosis of 0.48 (interquartile range, 0.1, 2.5) years. Freedom from death/transplantation was 86% (95% confidence interval [CI], 77.0–92.0) 1 year after presentation, 80% (95% CI, 69.0–87.0) at 10 years, and 78% (95% CI, 67.0–86.0) at 20 years. From multivariable analyses, risk factors for death/transplantation included symmetrical left ventricular hypertrophy at the time of diagnosis (hazard ratio, 4.20; 95% CI, 1.60–11.05; P =0.004), Noonan syndrome (hazard ratio, 2.88; 95% CI, 1.02–8.08; P =0.045), higher posterior wall thickness z score (hazard ratio, 1.45; 95% CI, 1.22–1.73; P <0.001), and lower fractional shortening z score (hazard ratio, 0.84; 95% CI, 0.74–0.95; P =0.005) during follow-up. Nineteen (23%) subjects underwent left ventricular myectomy. At a median of 15.7 years of follow-up, 27 (42%) of 63 survivors were treated with β-blocker, and 13 (21%) had an implantable cardioverter-defibrillator. Conclusions: The highest risk of death or transplantation for children with hypertrophic cardiomyopathy is within 1 year after diagnosis, with low attrition rates thereafter. Many subjects receive medical, surgical, or device therapy.